KEBERADAAN PEDAGANG KAKI LIMA SEBAGAI UNSUR PEMBENTUK KEGIATAN FUNGSIONAL KOTA - Nanang Yusroni (Universitas Wahid Hasyim, 2009)
Conflict between included area authority recently is being concerned by public/ Society hopes if the issues will be held and it is responsibility of the area authority because of regional autonomy. It is linked with the function as mediator, so the legal force could be done by them. Key Words: Street vendor, regional law, public